2010
DOI: 10.4049/jimmunol.1000574
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclooxygenase-2/Prostaglandin E2 Pathway Augments Activation-Induced Cytosine Deaminase Expression within Replicating Human B Cells

Abstract: Within inflammatory environments, B cells encountering foreign or self-Ag can develop tertiary lymphoid tissue expressing activation-induced cytosine deaminase (AID). Recently, this DNA-modifying enzyme was detected in nonlymphoid cells within several inflamed tissues and strongly implicated in malignant transformation. This study examines whether a cyclooxygenase 2 (COX-2) pathway, often linked to inflammation, influences AID expression in activated B lymphocytes. In this paper, we report that dividing human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 101 publications
(146 reference statements)
6
40
0
Order By: Relevance
“…Although the induction rate and protein amount varied ( Figure 3A,F), cell division and the presence of AID protein appeared to be linked: undivided clones did not up-regulate protein, whereas clones that had divided exhibited at least some protein up-regulation even if this was only after several cell cycles ( Figure 3F-G). Most cases showed a progressive increase in AID protein levels with each division ( Figure 3F), which is reminiscent of normal B cells, 37,38 and consistent with the idea that, within lymphoid sections, AID ϩ cells were principally Ki-67 ϩ (Figure 2 and Leuenberger et al 39 ). However, because most Ki-67 ϩ cells were AID Ϫ (Figure 2B), either only a small subset of cells are competent to express AID, which seems unlikely based on our in vitro stimulation data (Figure 3), or many of the Ki-67 ϩ CLL cells had not divided a sufficient number of times at the time of analysis to produce AID protein.…”
Section: Discussionsupporting
confidence: 82%
“…Although the induction rate and protein amount varied ( Figure 3A,F), cell division and the presence of AID protein appeared to be linked: undivided clones did not up-regulate protein, whereas clones that had divided exhibited at least some protein up-regulation even if this was only after several cell cycles ( Figure 3F-G). Most cases showed a progressive increase in AID protein levels with each division ( Figure 3F), which is reminiscent of normal B cells, 37,38 and consistent with the idea that, within lymphoid sections, AID ϩ cells were principally Ki-67 ϩ (Figure 2 and Leuenberger et al 39 ). However, because most Ki-67 ϩ cells were AID Ϫ (Figure 2B), either only a small subset of cells are competent to express AID, which seems unlikely based on our in vitro stimulation data (Figure 3), or many of the Ki-67 ϩ CLL cells had not divided a sufficient number of times at the time of analysis to produce AID protein.…”
Section: Discussionsupporting
confidence: 82%
“…We have reported that progeny from this response are characterized by elevated levels of CD23, CD86, CD38 and CD27 and sustained expression of CD20 (6). Interestingly, they show minimal evidence of plasmablast differentiation (6, 7) and bear some resemblance to the “marginal zone-like” cells observed within salivary glands of BAFF-overexpressing mice (8) and humans with Sjogren’s Syndrome (9). Importantly, during this TI response, dividing progeny contemporaneously upregulate activation-induced cytosine deaminase (AID) and several proteins of the cyclooxygenase 2 (COX-2) pathway (7).…”
Section: Introductionmentioning
confidence: 96%
“…These data were further substantiated by gene expression analyses showing no differential EP2 and EP4 gene expression of CD40-activated B cells compared to unstimulated B cells (data not shown). These findings are of special interest as it has been shown both for mouse and human B cells that under defined activation B cells express EP2 and EP4 receptors (43,44). Thus, it has to be addressed by further investigations whether the utilized method to generate CD40-activated B cells precludes the expression of EP2 and EP4.…”
Section: Discussionmentioning
confidence: 99%